Pengaruh Strategi Pengembangan SDM Terhadap Kinerja Karyawan - Rita Widjaja; Eddy Supriyatna (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
This research aims to determine the effect of training, work dicipline and organization communication toward employee performance. The sample used in the study amounted to 158 employees. The research method uses multiple linear regression analysis with the help of managing data using SPSS version 22 software. The results of this study indicate that training, organization communication partially have a significant effect on the employee performance, and work dicipline partially haven’t a significant effect on the employee performances. And training, work dicipline, organization communication a simultaneously have a significant effect on the employees Performances.